EFFICACY AND FINANCIAL VIABILITY OF PRIMARY PREVENTION OF ATOPIC DERMATITIS: PROTEIN-HYDROLYSATE-BASED FORMULAE - L. M. Ogorodova; F. I. Petrovskii; I. A. Deev; Y. A. Petrovskaya (Педиатрическая фармакология, 2013)
Primary prevention of allergy is an attractive aim due to high social, economic burden and increasing prevalence of allergic diseases. The up-to-date data strongly support the use of partially hydrolyzed whey formula for primary prevention of atopic dermatitis. This approach is effective and cost-saving both from societal and governmental health service perspectives. Pediatricians as well as parents of high risk children should be strictly aware of these data. Because of cost-saving effect of partially hydrolyzed whey formula governmental health service administrations should develop programs for primary prevention of atopic dermatitis with free supply of high risk children with this nutrition for first months of life.